2023
DOI: 10.3390/toxics11120984
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline-Induced Hepatotoxicity in Rats: Screening of Abnormal Metabolic Markers and Potential Mechanisms

Jing Sun,
Kai Zhang,
Yihui Yin
et al.

Abstract: Arecoline is a pyridine alkaloid derived from areca nut in the Arecaceae family. It has extensive medicinal activity, such as analgesic, anti-inflammatory, and anti-allergic. However, the toxicity of Arecoline limits its application. Most current studies on its toxicity mainly focus on immunotoxicity, carcinogenesis, and cancer promotion. However, there are few systematic studies on its hepatotoxicity and mechanisms. Therefore, this research explored the mechanism of hepatotoxicity induced by Arecoline in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Betel nut contains several active ingredients such as arecoline, which has been revealed the adverse effects on glucose and lipid metabolism. Animal studies have revealed that arecoline can induce insulin resistance by impairing insulin signaling and glucose uptake in skeletal muscle cells ( 41 , 42 ). Arecoline can also stimulate the production of pro-inflammatory cytokines, such as TNF-α and IL-6, which are known to lead to insulin resistance and MetS ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Betel nut contains several active ingredients such as arecoline, which has been revealed the adverse effects on glucose and lipid metabolism. Animal studies have revealed that arecoline can induce insulin resistance by impairing insulin signaling and glucose uptake in skeletal muscle cells ( 41 , 42 ). Arecoline can also stimulate the production of pro-inflammatory cytokines, such as TNF-α and IL-6, which are known to lead to insulin resistance and MetS ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dioxin-exposed humans vs. control Distinct metabolite profiles 24 urinary steroid-related biomarkers [69] Tributyltin in zebrafish Affected steroid biosynthesis metabolism Diverse [70,71] 6-propyl-2-thiouracil in zebrafish (Neuro-) developmental toxicity methionine↓, tyrosine↑, pipecolic acid↑ and lysophosphatidylcholine↑ [72] Arecoline in rats ∆ lipid metabolism, amino acid metabolism, and vitamin metabolism ∆ D-Lysine, N4-Acetylaminobutanal, and L-Arginine [73]…”
Section: Compound/substance and Model Mechanistic Insights Biomarkers...mentioning
confidence: 99%